Insecticidal effect of Cryptocarya alba essential o il on the housefly, Musca domestica L - Di Cosmo, Dania (2015)
The composition of the essential oil (EO) from Cryptocarya alba obtained by hydro distillation of fresh leaves was analyzed using gas chromatography (GC) and gas chromatography/mass spectros metry (GC/MS). The insecticidal effect of the oil on the hous e fly Musca domestica was evaluated by placing flies in a sealed glass jar containing a piece of EO - treated cotton yarn. The dose necessary to kill 50% of flies (LC 50 ) in 0.5 and 1 h was determined at 26 ± 1 °C. The essential oil from Cryptocarya alba show ed significant insecticidal p roperties [33.56 (7.06 - 159.50) mg/dm 3 (0.5 h) and 15.07 (5.29 - 42.91) mg/dm 3 (1 h)]. According to GC and GC/MS analysis a total of 38 compounds were identified. The composition of the Cryptocarya alba essential oil reported in t his study is different to that reported in other publications with 4 - terpineol (17.48%) ; 4 - (3,3 - dimethyl - but - 1 - ynyl) - 4 - hydroxy - 2,6,6 - trimethylcyclohex - 2 - enone (12.84%); 1,8 - cineole (7.90%); p - cymene (7.11%) and sabinene (6.80%), accounting for 52.13% o f the EO. The EO from Cryptocarya alba appears promising as a natural insecticide against houseflies.